MENGATASI TRAUMA PADA TINDAKAN KEKERASAN SEKSUAL PADA REMAJA PEREMPUAN - Ramadhan, Sandi; Ramadani, Dinda Frastica (Journal of Social Computer and Religiosity (SCORE), 2023)
One form of violence that is often experienced by teenagers, especially women is an act of sexual or sexual violence. Various forms and modes of perpetrators of violence Sexually this is done by groups of adults and even close family members. Facing this problem, it is necessary to need insight and a strategy to prevent the occurrence of sexual violence that afflicts teenagers, especially women. The research method used is library research. The main reason why women who become victims of sexual violence do not report is the bad stigma that society has on victims of violence. Suggestions from this research is that there should be mutual respect and care between men and women.